Interpersonal Functions of Taboo Words Uttered by the Characters in Vacation Movie - Bambang Irawan (Universitas Pamulang, 2019)
This reserached was aimed to figure out the interpersonal functions of taboo words in Vacation movie. Descriptive qualitative method was emploed in this research since the data were non-numerical data and the results of the research were explained in description which can be in forms of words, sentences, discourse, picture, etc. This research employed simak and catat technique to collect the data from Vacation movie. This is a technique for achieving data through listening carefully and then followed by taking note. In this research, the writer did the simak and catat technique by watching and listening to the movie carefully and then noted some words which were categorized as taboo words. Then, the data were analyzed and classified to figure out their interpersonal functions based on the theory of Zhao and Zhang (2016). As the result, there are at least three interpersonal functions of taboo words which are used and uttered by the characters in the Vacation movie. The interpersonal functions of taboo words which are found in the Vacation movie are to strengthen power and intensity, to vent pent-up emotions, and to show the acquaintance and intimacy.